1946
DOI: 10.1152/ajplegacy.1946.147.3.446
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hemorrhage on Tissue Metabolites

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2

Year Published

1950
1950
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 0 publications
0
18
2
Order By: Relevance
“…The blood levels of pyruvate and lactate remained significantly elevated above control values (Table II, Figures 3 and-4 (36). It seemed likely that hyperglycemia during oligemic shock was the result of glycogenolysis with depletion of liver glycogen while the fall in blood glucose during the impending or progressive stages was caused by depletion of liver glycogen (36).…”
Section: Metabolic Changes During Normovolemic Shockmentioning
confidence: 93%
“…The blood levels of pyruvate and lactate remained significantly elevated above control values (Table II, Figures 3 and-4 (36). It seemed likely that hyperglycemia during oligemic shock was the result of glycogenolysis with depletion of liver glycogen while the fall in blood glucose during the impending or progressive stages was caused by depletion of liver glycogen (36).…”
Section: Metabolic Changes During Normovolemic Shockmentioning
confidence: 93%
“…Hence, significant alterations in the high-ener gy phosphate compound yielding and consuming processes have been demonstrated in various species of experimental animals [3,9,20,24], As a consequence of such metabolic impairment, various functional changes have been shown to occur at the cellular and subcellular levels.…”
Section: Introductionmentioning
confidence: 99%
“…The fall in blood pressure which is observed with adenosine and inosine, although not directly related to the release of iron into the plasma, may be of some importance in circumstances occasioned by extensive hemorrhage or muscle injury. Evidence is available (8,9) which shows a breakdown of nucleic acids and nucleotides and an increase in inorganic phosphate in tissues such as blood and liver in hemorrhagic shock and in blood and muscle in traumatic shock (16). A sustained release into the blood stream of such compounds would serve to maintain a low blood pressure for a relatively long period of time with a resultant hypoxia in tissues such as liver.…”
Section: Discussionmentioning
confidence: 99%
“…iron (2) and since our in vitro studies have shown a relationship between the enzyme xanthine oxidase and the release of ferritin iron (1). Hemorrhagic or traumatic shock results in an accumulation of products of nucleotide catabolism (8,9). Therefore, determination of the end product of such catabolism, uric acid, would reveal the action of xanthine oxidase on hypoxanthine and xanthine resulting from such degradation products.…”
Section: Effect Of Hemorrhage or Trauma On Plasma Uric Acidmentioning
confidence: 99%